Mathematical modelling for gravity waves interactions coupled with localized water vapor and ozone in the atmosphere - Almohaimeed, Ahmed S. (Frontiers in Earth Science, 2024)
In the atmosphere, the interrelationship between dynamics and chemistry results in mutual influence and interaction. The behavior of internal gravity waves is influenced by the thermal effects caused by chemical components present in the atmosphere. In this investigation, the equations determining gravity waves are coupled with those characterizing the behavior of ozone and water vapor. To investigate the coupled equations, numerical analyses are conducted, and the resulting numerical results are presented. Internal gravity waves have been observed to influence the distribution of ozone and water vapor within the Earth’s atmosphere. It has been demonstrated, based on our findings, that wave fluctuations play a significant role in exerting a substantial effect. In addition, it has been observed that the influence of ozone and water vapor-induced heating on gravity waves is significant, particularly near the critical level where the mean flow induced by gravity waves plays a significant role.